LEAN PROCESS IMPROVEMENT IN HEALTHCARE: A STUDY USING VALUE STREAM MAPPING, THEORY OF CONSTRAINTS AND SIMULATION - Hazal Akbal; Nuri Özgür Doğan (International Journal of Management Studies)
In healthcare services, where human health is the primary concern, the principle of ''doing it right the first time'' is paramount. Waste and constraints in service delivery processes can directly impact patient health outcomes. This study aim is to examine the hospitalization process of the internal medicine department of an education and research hospital using value stream mapping (VSM), theory of constraints (TOC) and simulation (using Arena software). Initially, current and future patient flows were mapped using VSM. Constraints affecting these flows were determined using TOC, while simulation was used to assess the impact of a lean model on the system proposed through the future state map (FSM). Two scenarios were developed for the future state. The findings show the presence of numerous non-value-added steps in the existing system. A leaner patient flow was achieved by minimizing these inefficiencies through the proposed future state models, addressing problematic areas that hinder the flow. Non-value-added time (NVAT) was reduced by 44 percent in the first proposed scenario and by 72 percent in the second proposed scenario. Patients' length of stay (LoS) improved by 1 percent with the first model and decreased by 12 percent with the second model. Additionally, transfer time (TT) was decreased by 88 percent in the first scenario and by 92 percent in the second scenario. This study offers valuable insights and can serve as a roadmap for researchers, managers and decision-makers in the healthcare sector seeking to implement lean practices.